2021
DOI: 10.1080/02656736.2021.1874546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of hysteroscopic myomectomy of type 2 submucous fibroids greater than 4 cm in diameter via pretreatment with HIFU or GnRH-a

Abstract: Zhou (2021) Comparison of outcomes of hysteroscopic myomectomy of type 2 submucous fibroids greater than 4 cm in diameter via pretreatment with HIFU or GnRH-a ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A recent study by Liao et al 22 demonstrated that among the 31 patients with HIFU, the fibroids were downgraded to type 0 in 10 cases and type I in 5 cases. It shows that high intensity focused ultrasound (HIFU); reduces the size of the larger fibroids of type II and type III (close to endometrium) downgrade, so TCRM is safe and feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Liao et al 22 demonstrated that among the 31 patients with HIFU, the fibroids were downgraded to type 0 in 10 cases and type I in 5 cases. It shows that high intensity focused ultrasound (HIFU); reduces the size of the larger fibroids of type II and type III (close to endometrium) downgrade, so TCRM is safe and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…uterine submucosal fibroids <3 cm in length, the intervention time in the TCRM group was (34.2 ± 9.9) min, which was significantly lower compared to (40.0 ± 8.1) min in the PMWA group. The incidence of perioperative complications (postoperative fever) was 4.2%, 1 in 24 patients in the TCRM group, compared to 6 in 25 (24%) patients with postoperative abdominal pain in the PMWA group.A recent study by Liao et al22 demonstrated that among the 31 patients with HIFU, the fibroids were downgraded to type 0 in 10 cases and type I in 5 cases. It shows that high intensity focused ultrasound (HIFU); reduces the size of the larger fibroids of type II and type III (close to endometrium) downgrade, so TCRM is safe and feasible.…”
mentioning
confidence: 99%